W63+ and W64+ ionization by protons and photons - López, Sebastián David (2015)
In this work we investigate the ionization by proton impact, and photo ionization, involving highly charged ions of W, in particular the Ne-like W64+ and Na-like W63+ which are more likely to appear in ITER plasma. Total cross sections are calculated in the continuum-distorted-wave-eikonal-initial-state (CDW-EIS) approximation for ion-impact, while two completely different methods are used for photoionization: a perturbative dipolar aproach and the recently introduced Sturmian model.